Epidemiological and Clinical Insights into the Measles Outbreak in Diyala Province - Israa Tariq Mahmood; Mohammad Kassem Saleh; Abdulrazak Shafiq Hasan; Sarah Waleed Hamid; Firas Atta Jabar (Diyala Journal of Medicine, 2025)
Background: For more than sixty years, a safe and potent vaccine has been available; however, efforts to control measles through immunization are now endangered by a startling rise in cases both at home and abroad. Objectives: To explore epidemiological and clinical characteristics of measles outbreak during 2023-2024 in Diyala province, Iraq. Patients and Methods: This is a retrospective cross-sectional study that involved registering and following up the clinical case sheets of all measles cases admitted during the period from May 1st, 2023, to June 30th, 2024. A total of 5418 cases were included; among which 439 laboratory-confirmed cases. Clinical features were documented for a total of 652 cases. Results: The majority (4612, 85.1%) of patients aged ≤10 years, followed by those >10 -20 years of age (347, 6.4%); the difference was highly significant (p<0.001). Additionally, 5328 (98.3%) of patients were not vaccinated versus 90 (1.7%) who were vaccinated. The difference was highly significant (p<0.001). Patients with cough were significantly more than those without cough (99.5% versus 0.5%, p<0.001). Similarly, patients with coryza were significantly more than those without coryza (97.2% versus 2.8%, p<0.001). Likewise, conjunctivitis appeared in 616 (94.5%) patients, accounting for a significantly higher percentage compared to those without conjunctivitis (p<0.001). Conclusion: Unvaccinated people form an immunological gap that may act as an inlet for large measles outbreaks. Premarital screening of women for anti-measles IgG, adjusting the timing and number of measles vaccine doses, and increasing vaccination coverage plus initiation of an active surveillance system may reduce the rate of infection in the community. Keywords: Measles, Measles outbreak, Measles vaccine, Diyala province.